The morphological variation of Myzus persicae (Hemiptera: Aphididae) from peach and tobacco in Serbia and Montenegro - Vučetić Anđa; Petrović-Obradović Olivera; Stanisavljević Lj.Ž. (Archives of Biological Sciences, 2010)
Multivariate morphometric analysis was used to compare nine characteristics of 47 populations of Myzus persicae (Sulzer) originating from two host-plants, peach and tobacco, from 13 localities in 2004 and 34 localities in 2005, in Serbia and Montenegro. Multivariant discriminant analysis showed there to be a distinct discrimination between the populations from the peach and tobacco host-plants. The most important discrimination characteristics are the ultimate rostral segment length and processes terminalis length, which are greater in the aphids from tobacco than in those from peach. This is the first indication that in this part of Europe there are two subspecies: M. persicae (Sulzer) and M. persicae nicotianae Blackman. .